On the influence of the nozzle external configuration on the radiated screech and the decay of supersonic jets - CARLOMAGNO, Giovanni Maria; IANNIELLO, Carmine; VIGO, Paolo (Archives of Acoustics, 1981)
The behaviour of screeching jets exhausting from an axisymmetric con-vergent-divergent nozzle was studied. The nozzle had a 2.9 mm throat diameter and a. 1.95 theoretical exit Mach number. Compressed nitrogen was used to obtain nozzle stagnation pressures from 0.15 to 1.4 MPa (absolute), i.e. conditions of overexpanded, correctly expanded and underexpanded streams at the nozzle exit section. The jet exhausted into a free field room and tests were performed for several nozzle external configurations. Measurements were made in terms of noise level emitted by the jet and impact pressure downstream. It was found that in the weakly overexpanded and in the underexpanded regimes the nozzle external configuration influences markedly the screech intensity while it does not affect substantially its frequency. The latter generally decreases as the stagnation pressure increases; in particular in the weakly overexpanded regime two screeching frequencies are present for a given stagnation pressure. High intensity screech jets have down-stream impact pressures lower than low intensity ones and therefore higher decay rates. Even for correctly expanded jets, screech levels and impact pressures are configuration influenced. In the strongly overexpanded regime, several harmonically related spectral peaks are present whose frequencies increase for increasing stagnation pressure; they appear not to be substantially influenced by the nozzle configuration but correspond, rather, to pure shock noise.